Study the Factors affecting the Production of Coagulase Enzyme from Clinical Bacteria Isolated - Najemaddin Abdullah Hamad; Dhafer Alrawi (Indian Journal of Forensic Medicine & Toxicology, 2022)
This study included isolation and diagnosis of Coagulase Positive Staphylococci bacteria fromclinical samples of (21) samples from the Teaching Hospital for Women and Children in Ramadi andincluded nasal swabs, Ear swabs, Normel skin swabs, Wound swabs, Urine Swabs and Abscesses.These isolates were diagnosed according to phenotypic and biochemical tests and vatic. After diagnosingthe developing colonies, it was found the Gram-positive bacteria formed a percentage (71.42%) of theclinical samples out of the total isolates that gave growth on the culture media, and the Staphylococcipositive for the plasma coagulase enzyme (Coagulase Positive Staphylococci) was found. (71.42%) ofthe total Staphylococci bacteria obtained during isolation and diagnosis of clinical samples and a typeof Staphylococcus positive for coagulase (CPS), Staphylococcus. aureus, was diagnosed based on theSlide and Tube Coagulase Test.The sensitivity of CPS-positive staphylococcus to the antibiotic against the bacteria was tested and itwas found that the most effective antibiotic against S. aureus bacteria was Azithromycin as well as theantibiotic Gentamycin, as indicated by S. aureus has demonstrated resistance to Erythromycin as wellas Ciprofloxacin.The different conditions for the production of the plasma coagulase enzyme (Coagulase) for the bacterialisolate of local number (5) were studied, and it was noticed that there is a great similarity in theseconditions except for some differences. The study and it was noticed that the appropriate temperature inthe production of the enzyme for the local bacterial isolate number (5) is the temperature (35) C, and itwas noticed that the pH that led to the increase in the production of the enzyme is (PH10).After (24hr)incubator , and the results were consistent in terms of good production of the enzyme in the mentionedisolation when using a incubator shaker at a speed (100) .